2023
DOI: 10.5194/egusphere-egu23-12021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of pore network architecture on the efficiency of microbial soil organic matter decomposition

Abstract: <p>Microbial decomposition of soil organic matter is one of the major drivers of nutrient and carbon cycling in terrestrial ecosystems. Soils are spatially heterogeneous habitats built up hierarchically from µm- to mm-sized aggregates that provide a complex pore system. An enormous diversity of microbes occupies this physically and chemically heterogeneous pore space. Although, in recent decades the consensus has largely been established, that microbial processes are strongly affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The rhizosphere priming effect, influenced by plant roots and rhizosphere activities, plays a crucial role in regulating global carbon and nitrogen cycles (Pausch et al, 2016). The architecture of soil pore networks significantly impacts microbial processes, including the decomposition of soil organic matter (Rath et al, 2023). Rhizodeposition accelerates SOM decomposition and N immobilization, even in plant growth competition (Schenck zu SchweinsbergMickan et al, 2012).…”
Section: How Soil Pores Influence Processes Like Soil Organic Matter ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The rhizosphere priming effect, influenced by plant roots and rhizosphere activities, plays a crucial role in regulating global carbon and nitrogen cycles (Pausch et al, 2016). The architecture of soil pore networks significantly impacts microbial processes, including the decomposition of soil organic matter (Rath et al, 2023). Rhizodeposition accelerates SOM decomposition and N immobilization, even in plant growth competition (Schenck zu SchweinsbergMickan et al, 2012).…”
Section: How Soil Pores Influence Processes Like Soil Organic Matter ...mentioning
confidence: 99%
“…The soil pore space's architecture and uneven substrate distribution significantly impact microbial processes. Rath et al (2023) found that pore network architecture and properties like average node degree, shortest path length, and clustering coefficient affect microbial OM decomposition efficacy. The structure of soil pores also affects nutrient solubility, microbial activity, and root development.…”
Section: How Soil Pores Influence Processes Like Soil Organic Matter ...mentioning
confidence: 99%